POSTMODERNISM AND SCEPTICISM IN THE REPRESENTATIONAL POWER OF LANGUAGE (Philological Studies, 2019)
This article is dedicated to problematizing the referentail function of language and written text, i.e. the scepticizm in their reliability in recognizing and describing reality, which is one of the fundamental poetic characteristics of postmodernism. In this article we elaborate on several segments of the philosophical, literary-theoretical and linguistic conceptions and categories (those of Platon, Locke, Wittgenstein, Derrida, Lacan, Lyotard Baudrillard, Compagnon and other thinkers), such as: theories of real cognition; the relationship between information and meaning; the breadth of meaning versus the narrowness of symbols; the arbitrariness of signs; language games; the deregulation of communication; the crisis in the idea of encyclopedism as definite, valid and only knowledge. As an illustration of the theoretical thesis, we use several postmodern texts (the novels "Alphabet for the Unruly", and "The Navel of the World" by Venko Andonovski; the novel "Descriptor" by Ermis Lafazanovski; the novel "Khazar Dictionary" by Miodrag Pavik; and the story collection "The God of Language and other stories" by Sreten Ugricik) which in their openness and imprecision are most adequate in describing the arbitrariness of meaning; the variation of the concept of truth; the inadequacy of the three types of written word in the accurate naming of things; the volatility in meaning of the words which are merely a culturological product and point to the different histories and contexts of their use. The interpretative part of this article implies the principle of comparative analysis of works from the Macedonian and Serbian literature.
Keywords: language, written word, postmodernism, Venko Andonovski, Ermis Lafazanovski, Milorad Pavik, Sreten Ugricik, communication, arbitrariness of sign, language games, hyper- reality, encyclopedism